THE ROLE OF THE DEPARTMENT OF THE ENVIRONMENT SIKKA DISTRICT IN DEALING WITH WASTE MANAGEMENT IN THE WAIOTI SUB-DISTRICT - Maria Kusmiati; Danar Aswim (Institut Pendidikan Indonesia, 2023)
This stud aims to determine the etent of the role and inhiiting factors of the Sikka egenc Enironmental Serice in dealing ith aste management in the aioti illage. This research method as carried out ith a ualitatie descriptie approach. The data sources used are primar data sources and secondar data sources. The informants inoled in this research ere the Secretar of the Enironmental Serice the ead of the aste management section the drier of the garage collector the aioti illage head and the communit. Data collection techniues used are oseration interies and documentation techniues. Data analsis techniues include Data eduction Data Displa and onclusion Draingerfication. ased on the results of the research that the Sikka egenc enironmental serice has carried out its role namel proiding socialiation and education and proiding serices to the communit in handling aste management in the aioti sudistrict the enironmental serice has carried out its role ell in aste management in the communit enironment. oeer there are man ostacles eperienced in carring out their role namel the lack of infrastructure the carring capacit of ehicle moiliation funds lack of understanding of the communit. This research suggests to the Sikka district enironmental serice to continue to proide socialiation and more superision in the communit enironment and proide training to the communit to reccle to e made into highalue materials so as to reduce aste that is scattered around the communit enironment.